Time course from first symptom to treatment in patients with non-small cell lung cancer referred for radiotherapy: a report by the CHART Steering Committee. Issue 12 (December 1996) - Dische, S.; Gibson, D.; Parmar, M.; Saunders, M. I.
Abstract : BACKGROUND: Only a small proportion of patients with non-small cell lung cancer (NSCLC) attending radiotherapy centres were suitable for inclusion in a randomised trial which compared continuous hyperfractionated accelerated radiotherapy (CHART) with conventional radical radiotherapy. As this was thought to be partly due to delays in the referral of patients to clinical oncologists, a prospective study was performed to determine the interval between first report of symptoms and first radiotherapy treatment in patients with NSCLC. METHODS: The time course from first symptom to treatment was determined in all patients with NSCLC attending 10 cancer centres for radiotherapy to a primary tumour in a three month period. RESULTS: Only 5% of 484 patients were suitable for the trial of radical radiotherapy. The principal causes for exclusion were poor general condition (37%), too large a tumour (27%), and extrathoracic metastases (19%). The median time from first symptom to diagnosis was 13 weeks, from first symptom to first treatment 19 weeks, and from diagnosis to first treatment five weeks. In a quarter of the patients these intervals were greater than 25, 33 weeks, and nine weeks, respectively. CONCLUSION: The reason for these long intervals needs investigation since earlier diagnosis and more immediate referral for consideration of treatment might increase the number of patients with NSCLC suitable for radical radiotherapy.